Treating gout in patients with comorbidities. (December 2011) - Gow, Peter
Gout causes extremely painful episodes of acute inflammatory arthritis, joint damage and chronic tophaceous disease. Comorbidities are common, even though their exact relationship with hyperuricemia and gout is currently uncertain. These comorbidities need to be taken into account in people who have them when treating their gout with pharmacological and nonpharmacological management, including lifestyle modification. Gout can be successfully managed in these people with consideration of the influence of medications used for gout and their impact on the components of the metabolic syndrome and on chronic renal impairment. The impact of medicines used to treat the comorbidities upon the management of acute gout, and on the requirement for reduction of uric acid to the target range of less than 6 mg/dl (0.36 mmol/l), is also important, along with drug interactions. Although there is a shortage of randomized controlled trials to guide treatment, attention to these factors, including the incorporation of patient preferences, should lead to better adherence to therapy and improved health outcomes.